2020
DOI: 10.3389/fphys.2020.00400
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an A-Type Muscarinic Acetylcholine Receptor and Its Possible Non-neuronal Role in the Oriental Armyworm, Mythimna separata Walker (Lepidoptera: Noctuidae)

Abstract: Muscarinic acetylcholine receptor (mAChR) regulates many neurophysiological functions in insects. In this report, a full-length cDNA encoding an A-type mAChR was cloned from the oriental armyworm, Mythimna separata. Pharmacological properties studies revealed that nanomolar to micromolar concentrations of carbachol or muscarine induced an increase of intracellular Ca 2+ concentration ([Ca 2+ ] i), with the EC 50 values of 124.6 and 388.1 nM, respectively. The increases of [Ca 2+ ] i can be greatly blocked by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 83 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…However, there is no insecticide that targets insect mAChRs to date 46,47 . Our previous research showed the presence of A‐mAChR protein on the oocyte membrane of M. separata , which indicates a possible non‐neuronal function of A‐mAChR in the reproductive system 32 . However, nothing is known about the source of ACh and the main components of the cholinergic system in the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is no insecticide that targets insect mAChRs to date 46,47 . Our previous research showed the presence of A‐mAChR protein on the oocyte membrane of M. separata , which indicates a possible non‐neuronal function of A‐mAChR in the reproductive system 32 . However, nothing is known about the source of ACh and the main components of the cholinergic system in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Our previous research showed the presence of A-mAChR protein on the oocyte membrane of M. separata, which indicates a possible non- neuronal function of A-mAChR in the reproductive system. 32 However, nothing is known about the source of ACh and the main components of the cholinergic system in the ovary. Thus, clarification of the difference between the neuronal and non-neuronal cholinergic systems is important to supplement our understanding of the non-neuronal role of ACh in insects and to lay the foundation for exploring novel insecticides targeting the nonneuronal cholinergic system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations